2017
DOI: 10.1016/j.jclepro.2017.04.156
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and adsorption properties of magnetic chitosan composite adsorbent for Cu 2+ removal

Abstract: Water pollution caused by Cu 2+ ions poses a significant threat to the ecosystem and human health, hence the development of highly cost-effective, highly operation-convenient and highly efficient natural polymer-based adsorbents is urgently needed. To overcome this serious problem, a novel cost-effective magnetic chitosan composite adsorbent (CsFeAC) was prepared with magnetic macroparticles and highly porous activated carbon carrier using the sol-gel method. Several methods, namely SEM, BET, FTIR, XRD, TGA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…Various methods based on membrane technologies, adsorption, biodegradation, distillation, photocatalysis and other approaches, have been utilized for purification and remediation of the polluted water (Hui et al, 2018;You et al, 2018). Among these approaches, adsorption process is regarded as an efficient alternative, due to its simplicity of design, wide adaptability, convenience and ease of operation, especially when the adsorbent is relatively low-priced and readily available (Li et al, 2017;Rafatullah et al, 2010;Thakur et al, 2017;Zahir et al, 2017;Zhou et al, 2018). However, developing the adsorbents with low cost, easy preparation and high efficiency is still the problem and challenge in dye adsorption application (Yang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Various methods based on membrane technologies, adsorption, biodegradation, distillation, photocatalysis and other approaches, have been utilized for purification and remediation of the polluted water (Hui et al, 2018;You et al, 2018). Among these approaches, adsorption process is regarded as an efficient alternative, due to its simplicity of design, wide adaptability, convenience and ease of operation, especially when the adsorbent is relatively low-priced and readily available (Li et al, 2017;Rafatullah et al, 2010;Thakur et al, 2017;Zahir et al, 2017;Zhou et al, 2018). However, developing the adsorbents with low cost, easy preparation and high efficiency is still the problem and challenge in dye adsorption application (Yang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…They also cause secondary pollution in the environment due to their small dimensions [159,160]. In order to eliminate these disadvantages, magnetic chitosan composite with macro particles was developed by adding porous activated carbon for the removal of copper ions and it showed successful results with a maximum capacity for adsorption at 216.6 /mg with 95% efficiency [95]. Elwakeel et al modified magnetic chitosan with TEPA for the adsorption of uranium ions and the maximum adsorption capacity reached to 1.8 mmol/g [161].…”
Section: Chemically Modified Chitosan For the Removal Of Heavy Metal mentioning
confidence: 99%
“…Li Jixiang et al [97] (2017) reported novel efficient and cost-effective magnetic polymer composite macro particles with highly porous activated carbon carrier adsorbent (CsFeAC) was synthesized by using the sol-gel method. It was found that synthesized polymer composite have higher specific surface area and lower crystalinity which enhance the absorption capacity.…”
Section: Literature Surveymentioning
confidence: 99%